Implementation of Multicultural Education in Strengthening Inter Religious Tolerance at Taman Harapan High School Malang City - Ummami, Farida; M. Nurul Humaidi; Fahrudin Mukhlis (Mudir : Jurnal Manajemen Pendidikan, 2023)
Multicultural education is education that teaches diversity in tolerance in various groups that have different ethnic, religious and cultural backgrounds.. This research article aims to examine the process of multicultural education in strengthening inter-religious toleration at Taman Harapan High School, Malang City. The research used is a qualitative approach with a case study type. The data were collected by observing and interviewing. The results of the research, as seen from the description of observations and interviews, are the forms of implementation multicultural applied at Taman Harapan High School, such as (1) Maintenance of religion classes is held every Tuesday, (2) Learning practices can be carried out by all religions, (3) Inclusivism and the initiation of diversity activities in schools in a fair and equal manner, by worship together on Fridays., (4) Decorating activities is held for every major religious event, (5) Students can participate in various school activities such as sport, making crafts, and celebrating independence on 17th of August. After understanding the multicultural education provided by the teacher and the school, the students were shown to have a high tolerance for being friends with everyone, regardless of their backgrounds. It is reflected in the attitudes and behavior students apply daily in school.